(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
the article analyzes the history of the University of the Third Age, the importance of education for people of the third age, considers the views of representatives of different eras, the opinions of scientists, the psychological characteristics of people belonging to the category of the third age.